Development of novel vaccines against Enterovirus-71 - Yee, Isabel Pin Tsin *; Poh, Chit Laa * (MDPI, 2015)
The hand, foot and mouth disease is caused by a group of Enteroviruses such as Enterovirus 71 (EV-A71) and Coxsackievirus CV-A5, CV-A8, and CV-A16. Mild symptoms of EV-A71 infection in children range from high fever, vomiting, rashes and ulcers in mouth but can produce more severe symptoms such as brainstem and cerebellar encephalitis, leading up to cardiopulmonary failure and death. The lack of vaccines and antiviral drugs against EV-A71 highlights the urgency of developing preventive and treatment agents against EV-A71 to prevent further fatalities. Research groups have developed experimental inactivated vaccines, recombinant Viral Protein 1 (VP1) vaccine and virus-like particles (VLPs). The inactivated EV-A71 vaccine is considered the safest viral vaccine, as there will be no reversion to the infectious wild type strain. The recombinant VP1 vaccine is a cost-effective immunogen, while VLPs contain an arrangement of epitopes that can elicit neutralizing antibodies against the virus. As each type of vaccine has its advantages and disadvantages, increased studies are required in the development of such vaccines, whereby high efficacy, long-lasting immunity, minimal risk to those vaccinated, safe and easy production, low cost, dispensing the need for refrigeration and convenient delivery are the major goals in their design.